Identifying the intervention mechanisms of polydatin in hyperuricemia model rats by using UHPLC-Q-Exactive Orbitrap mass spectroscopy metabonomic approach - Ge, Xueli; Su, Zhenguo; Wang, Yuhao; Zhao, Xue; Hou, Kaifei; Zheng, Shuna; Zeng, Pengjiao; Shi, Zhongqi; Hu, Senhao; Wang, Yuqing; Zhou, Mengchen; Zhang, Jiayu; et al. (Frontiers in Nutrition, 2023)
Introduction Polydatin is a biologically active compound found in mulberries, grapes, and Polygonum cuspidatum, and it has uric acid-lowering effects. However, its urate-lowering effects and the molecular mechanisms underlying its function require further study. Methods In this study, a hyperuricemic rat model was established to assess the effects of polydatin on uric acid levels. The body weight, serum biochemical indicators, and histopathological parameters of the rats were evaluated. A UHPLC-Q-Exactive Orbitrap mass spectrometry-based metabolomics approach was applied to explore the potential mechanisms of action after polydatin treatment. Results The results showed a trend of recovery in biochemical indicators after polydatin administration. In addition, polydatin could alleviate damage to the liver and kidneys. Untargeted metabolomics analysis revealed clear differences between hyperuricemic rats and the control group. Fourteen potential biomarkers were identified in the model group using principal component analysis and orthogonal partial least squares discriminant analysis. These differential metabolites are involved in amino acid, lipid, and energy metabolism. Of all the metabolites, the levels of L-phenylalanine, L-leucine, O-butanoylcarnitine, and dihydroxyacetone phosphate decreased, and the levels of L-tyrosine, sphinganine, and phytosphingosine significantly increased in hyperuricemic rats. After the administration of polydatin, the 14 differential metabolites could be inverted to varying degrees by regulating the perturbed metabolic pathway. Conclusion This study has the potential to enhance our understanding of the mechanisms of hyperuricemia and demonstrate that polydatin is a promising potential adjuvant for lowering uric acid levels and alleviating hyperuricemia-related diseases.